Career Development, Career Maturity and Career Success in Generation Z: A Systematic Review - Muhamad Ali; Septriana Rachmawati; Yoan Zelika; Neng Pebri Yanti; Wilson Bangun (Future Science, 2023)
A career for someone is a record of patterns of professional work experience that influence all aspects of their life. This is in line with the views of Generation Z on careers. This generation views career development, career maturity, and career success realistically and rationally. Where they seek clear paths for their career growth and progress. They want stability and confidence in their careers. They have a principle that work life must be balanced with their personal life. Their career choices are always made by their hearts. They prioritize the principle of heart joy over being pushed by work. Generation Z will not hesitate to quit their job if it makes them uncomfortable. This article discusses the perspective of Generation Z on career development, career maturity, and career success using a systematic literature review approach. Relevant studies published come from three main academic databases; Science Direct, Google Scholar, and Research Gate